Secular change in TTG compositions: Implications for the evolution of Archaean geodynamics - Johnson, Tim; Kirkland, Chris; Gardiner, Nicholas; Brown, M.; Smithies, R.; Santosh, M. (Elsevier BV, 2019)
It is estimated that around three quarters of Earth's first generation continental crust had been produced by the end of the Archaean Eon, 2.5 billion years ago. This ancient continental crust is mostly composed of variably deformed and metamorphosed magmatic rocks of the tonalite–trondhjemite–granodiorite (TTG) suite that formed by partial melting of hydrated mafic rocks. However, the geodynamic regime under which TTG magmas formed is a matter of ongoing debate. Using a filtered global geochemical dataset of 563 samples with ages ranging from the Eoarchaean to Neoarchaean (4.0–2.5 Ga), we interrogate the bulk rock major oxide and trace element composition of TTGs to assess evidence for secular change. Despite a high degree of scatter in the data, the concentrations or ratios of several key major oxides and trace elements show statistically significant trends that indicate maxima, minima and/or transitions in the interval 3.3–3.0 Ga. Importantly, a change point analysis of K2O/Na2O, Sr/Y and LaN/YbN demonstrates a statistically significant (>99% confidence) change during this 300 Ma period. These shifts may be linked to a fundamental change in geodynamic regime around the peak in upper mantle temperatures from one dominated by non-uniformitarian, deformable stagnant lid processes to another dominated by the emergence of global mobile lid or plate tectonic processes by the end of the Archaean. A notable change is also evident at 2.8–2.7 Ga that coincides with a major jump in the rate of survival of metamorphic rocks with contrasting thermal gradients, which may relate to the emergence of more potassic continental arc magmas and an increased preservation potential during collisional orogenesis. In many cases, the chemical composition of TTGs shows an increasing spread through the Archaean, reflecting the irreversible differentiation of the lithosphere.